(untitled) (Research, Society and Development, 2021)
Understand the reality of a high-risk pregnancy, as well as the sensations, fears and concerns by women during this period. The paper presents a qualitative, exploratory and descriptive study based on the testimonies of seven women diagnosed with pre-gestational cardiovascular diseases diagnosed as high-risk expectant. The technique of thematic discourse analysis used three methodological figures: The Main Idea, Key Expressions and the Collective Subject Discourse. The Research Ethics Committee approved the study. From the statements, seven topics were created, presented by summary tables consisting of Main Ideas, which, in turn, revealed the principal meanings of the senses. Seven women were interviewed, aged between 24 and 41. All women started in Primary Care and were later referred to the high-risk pregnancy referral regarding prenatal care. New discussions are needed about care practices for high-risk pregnant women that favor humanized, critical, qualified care and the formation of effective bonds so that the period can be lived safely and autonomously.